PT Jamkrindo Surety Bond Product Marketing Strategy 2024-2026 - Agustinus Handoko; Anggun Pesona Intan; Pepey Riawati Kurnia (International Journal of Social Service and Research, 2023)
The Indonesian government, under the leadership of President Joko Widodo for two terms, gave significant emphasis on infrastructure development, as reflected in the annual infrastructure capital expenditure. Infrastructure development aims to promote balanced development and open up new economic areas. In addition to infrastructure projects, the government also allocates a portion of the capital expenditure to strategic projects. The procurement process for goods and services, both for infrastructure development and capital expenditure, requires Surety Bonds issued by guarantee companies or Bank Guarantees issued by banks. PT Jamkrindo is one of the providers of Surety Bond products, however, its marketing strategy is not aligned with the marketing objectives of increasing the volume of guarantees and profitability. Therefore, a new marketing strategy for Surety Bond products is needed, utilizing the Mullins 4C model approach: context, customer, company, and competitor. These four aspects are analyzed using macro analysis, industry analysis, consumer decision-making process (CDMP), brand image, points of parity, and points of difference. Through this analysis, a new marketing strategy for Surety Bond products is formulated.